Quality assessment and shelf life modeling of pulsed electric field pretreated osmodehydrofrozen kiwifruit slices - Efimia Dermesonlouoglou; Ismini Zachariou; Varvara Andreou; Petros S. Taoukis (International Journal of Food Studies)
The objective of this work was to investigate the potential use of pulsed electric field (PEF) in combination with osmotic dehydration (OD) as a pre-freezing step and to evaluate the effect on quality characteristics and shelf life of frozen kiwifruit. Peeled kiwifruit was subjected to PEF (1.8 kV/cm), sliced and treated in OD-solution (containing glycerol, maltodextrin, trehalose, ascorbic acid, calcium chloride, citric acid, sodium chloride; 1/5 (wfruit/wsolution)) for 30 and 60 min at 35 °C. Combined, PEF only and OD only treated samples as well as nontreated and blanched (80 °C, 60 s) samples were frozen and stored at constant (-5, -10, -15, -25 °C) and dynamic temperature conditions (-18 °C-3 d, -8 °C-2.5 d, -15 °C-3 d). Quality of frozen samples was evaluated by means of drip loss, colour, texture, vitamin C and sensory evaluation (1-9 scale); and shelf life (SL) was calculated. Nontreated and blanched samples presented high drip loss and tissue softening (instrumentally measured as Fmax decrease). The tissue integrity was well retained in all osmotically pretreated samples. PEF pretreatment caused increase of fruit whiteness (increase of L value) and yellowness (a and/or b value increase); SL calculation was based on colour change. All OD samples had high vitamin content (24.6 mg/100 g fresh material compared to 138-154 mg/100 g osmodehydrated material); PEF led to 93% (of the initial) vitamin retention; blanched samples showed the lowest retention (86.9% of the initial) (criteria for SL calculation). OD and combined PEF-OD treatment increased the shelf life of frozen kiwifruit (up to 3 times; based on sensorial criteria). The developed kinetic models for colour change, vitamin loss, and sensory quality deterioration were validated at dynamic temperature conditions. PEF pretreated OD (at significantly shorter time, 30 min compared to 60 min) kiwifruits retained optimum quality and sensory characteristics. PEF and OD could be used as a preprocessing step of good quality, longer shelf life kiwi sliced frozen products.